AL-‘UQUD AL-MURAKKABAH IMPLEMENTATION ON AKAD AL MURABAHAH WA ARRAHN AS A SHARIA BANKING PRODUCT INNOVATION - Bagya Agung Prabowo (Diponegoro Law Review, 2019)
This article aims to determine the application of al-uqud al-murakkabah on akad al murabahah wa arrahn in sharia banking product innovation. This study uses analytic methods based on doctrinal content, by applying four types of legal approaches, namely: (i) historical / historical; (ii) Jurisprudence / philosophy; (iii) comparison; and (iv) analytical and critical. In addition, a harmonious approach is needed to align innovation of sharia banking products with sharia compliance principles. the conclusions in this study are: 1) The implementation of al-ququd al-murakkabah as an innovation of Islamic banking products by the majority of Hanafiyah scholars, some opinions of Malikiyah scholars, Shafi'i scholars, and Hanbali are of the opinion that law is legal and permissible according to Islamic law, 2) The implementation of al-uqud al-murakkabah in the Murabahah wa ar Rahn contract is not in accordance with the principles of sharia compliance. Because the al Murabahah wa ar Rahn contract combines several contracts that cause usury or resemble usury, such as primarily combining the murabahah contract with the qardh contract, in addition to the wakalah contract and rahn contract.